Pelatihan Akuntansi UMKM Bagi Usaha Mikro Kecil Menengah (UMKM) Di Kelurahan Padang Nangka Kecamatan Singaran Pati Kota Bengkulu - Charolina, Ovita; Gustiawan , Yoga; Prasetio , Irawan (Jurnal Kewirausahaan dan Bisnis, 2021)
This research explores the role of cooperatives in the economic development of Bajak II Village, Central Bengkulu Regency, with a focus on MSME accounting training for micro, small and medium enterprises (MSMEs) in Padang Nangka Village, Singaran Pati Sub-district, Bengkulu City. Cooperatives are considered to have great potential in strengthening the local economy by providing financial services, facilitating the marketing of local products, and providing training and mentoring to their members. Through a qualitative and quantitative approach, this study aims to analyze the contribution of cooperatives in advancing the MSME sector at the village and kelurahan levels. Data were collected through interviews, observations, and statistical analysis, to gain a holistic understanding of the role of cooperatives as well as the impact of accounting training on MSMEs in the region. The results of this study are expected to provide deep insights into effective cooperative development and training strategies in supporting the economic growth of MSMEs at the local level.